Die Keramik der früh-Gazǐra v- Alt-Gazǐ II-zeit - Schmidt, Conrad (Studien zur Urbanisierung Nordmesopotamiens, 2013)
In the fourth volume of "Studies on the Urbanization of Northern Mesopotamia" (SUN), Series A, Conrad Schmidt addresses the pottery from the early Gazira V to Old Gazira II periods (approx. 2100 to 1600 BC) from the excavations in the central upper town of Tall Mozan/Urkeš in NE Syria. These periods correspond to the late Early and much of the Middle Bronze Age and thus include the transition from the third to the second millennium BC Schmidt's study includes the evaluation of all stratified pottery from the relevant phases of use in Tall Mozan and, with its complete and unselected description, pursues a new methodical approach in Near Eastern archeology.In addition to numerous statistics, tables and diagrams, the processing of the data on goods, vessel types, form type groups, form types and ware form types in the respective use phases extended by an extensive catalog with over 4360 drawings Investigations, including a relatively chronological digression on the most important usage phase of the investigation period, C 7 (Early Gazira V period), and a regional and above all supra-regional comparison with pottery from the same period from other sites supplement the evaluation and make an important contribution to the discussion about the synchronicity of Egyptian, Levantine and Mesopotamian chronology, which is still difficult to establish.